2017
DOI: 10.18203/2319-2003.ijbcp20171090
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice toward adverse drug reaction reporting among practicing clinicians at a tertiary care hospital

Abstract: Background: Pharmacovigilance has evolved as an important tool for dealing with Adverse Drug Reactions (ADRs) both in pre-marketing and post-marketing scenario. Underreporting of ADRs at our Adverse drug reaction Monitoring Centre (AMC) led us to conduct this study to assess Knowledge, Attitude and Practice (KAP) of the practicing clinicians at our tertiary care Pt. J.N.M. Medical College associated Dr. B.R.A.M. Hospital, Raipur, Chhattisgarh, India, towards ADRs reporting.Methods: This was a cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…Similar findings have been reported from India (Todar et al., 2017), where only 40% (40/100) respondents knew about the hospitals' reporting systems. In our study, most respondents, particularly nurses, reported knowing to whom to report an incident or error (Figure 1), whereas a Saudi Arabian study in June 2013 reported that the majority of respondents did not report errors because they did not know who the responsible persons were (Abdel‐Latif, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings have been reported from India (Todar et al., 2017), where only 40% (40/100) respondents knew about the hospitals' reporting systems. In our study, most respondents, particularly nurses, reported knowing to whom to report an incident or error (Figure 1), whereas a Saudi Arabian study in June 2013 reported that the majority of respondents did not report errors because they did not know who the responsible persons were (Abdel‐Latif, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, this was the first study in India designed to assess the Clinician's opinion (mindset) on the strategic implementation of PvPI-Helpline (Toll-Free) number and concise ADR form in Inpatient case sheets. Clinicians across studies felt that ADR reporting was very necessary 18 but only 70%-78% of them knew that such systems were already in place [18][19][20][21] .…”
Section: Resultsmentioning
confidence: 99%